Desain Sudut Elevasi Panel Surya Untuk Penerangan Jalan - Rosalina (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2020)
Sun light that appears in the morning carries electron molecules which will radiate its rays across the surface of the earth. Utilizing this radiation from the sun, we will get the electric power carried by electromagnetic waves if we put it on the solar panel that we have prepared by directing it perpendicular to the rotating motion of the sun. The design of the solar panel elevation angle uses the Arduino ATmega2560 as a system controller and solar panel sensors to sense the direction of the sun's moti on. The purpose of this design is to find the maximum radiation based on the time of sunrise and sunset as well as the azimuth and elevation angles so as to increase battery charge. The results of the solar panel testing by making a computer programming application and assembling a rotary device using a motor and solar sensor were obtained the greatest power in the second test, which was 1.01867Watt, so that the battery charging time took ± 7 hours. The maximum radiation received on the solar panel is at an angle of 110o for azimuth, while for an elevation of 1o, it is 1233.0 (MJ / m2 / day). The amount of total radiation received by the solar panels for one day is 10690.2448Wms-2 in the third test. This means that directing the solar panels perpendicularly can maximize the work of the solar panels.